Aberrant tolerogenic functions and proinflammatory skew of dendritic cells in STAT1 gain-of-function patients may contribute to autoimmunity and fungal susceptibility - Parackova, Zuzana; Zentsova, Irena; Vrabcova, Petra; Sediva, Anna; Bloomfield, Marketa (Clinical immunology (Orlando, Fla.), 2023)
STAT1 gain-of-function (GOF) mutations underlie an inborn error of immunity hallmarked by chronic mucocutaneous candidiasis (CMC). Beyond the fungal susceptibility, attributed to Th17 failure, over half of the reported patients suffer from autoimmune manifestations, mechanism of which has not been explained yet. We hypothesized that the STAT1 mutations would affect dendritic cells' (DCs) properties and alter their inflammatory and tolerogenic functions. To test the hypothesis, we generated monocyte-derived DCs (moDCs) and tolerogenic DCs (tDCs). Functional and signaling studies, co-culture experiments and RNA sequencing demonstrated that STAT1 GOF DCs were profoundly altered in their phenotype and functions, characterized by loss of tolerogenic functions, proinflammatory skew and decreased capacity to induce Th17. Cytokine signaling, autophagy and metabolic processes were identified as the most prominently altered cellular processes. The results suggest that DCs are directly involved in STAT1 GOF-associated immune pathology, possibly contributing to both autoimmune manifestations and the failure of antifungal defense.
Keywords: transkripční faktor STAT1; STAT1; Humans; Dendritic cells; dendritické buňky; Gain of Function Mutation; Autoimmunity; mutace; CMC; Candidiasis, Chronic Mucocutaneous; lidé; kandidóza chronická mukokutánní; Candidiasis; Dendritic Cells; Ruxolitinib; autoimunita; aktivační mutace; Tolerogenic; Mutation; Autophagy; STAT1 Transcription Factor